Humanisme dalam Ekranisasi Dilan 1990: Humanism in the ecranization of “Dilan 1990” film - Suseno, Suseno; Neina, Qurrota Ayu; Zuliyanti, Zuliyanti (Journal of Literature and Education, 2023)
The purpose of this study is to explain the humanist values contained in the novel Dilan 1990. This study used a qualitative descriptive approach with research steps, including finding and collecting, determining, identifying elements, analyzing humanist values, and compiling reports of results and outputs. Data collection techniques are literature study techniques, listen and take notes. Data analysis techniques were carried out by means of data reduction, data presentation, and data inference. The results of this study indicate that there are changes in the form of variations, additions, and subtractions. The humanist values in this ecranization include humanist values in the family realm, education realm, friendship realm, and family realm and the context of friendship. The impact of humanist values that emerge are (1) the perspective of the Motorcycle Gang, (2) naughty students, but cute and smart, (3) attitudes towards spouses or girlfriends, (4) the aspiration to become wise parents, (5) become humanist personality is fun.